Generational Conflict in the Workplace: An Analysis of Organizational Adaptation to Differences in Millennial and Gen Z Work Patterns - Nur Shinta; Flanella Azzahra Putri; Willis Arestria Ayu Anggini; Srikandi Wiwaha; Citra Anisa Tika Putri (CV. Proaksara Global Transeduka, 2025)
Generational conflict in the workplace is an increasingly prominent phenomenon as multiple generations such as Baby Boomers, Generation X, Y (Millennials), and Z converge in the same work environment. Differences in values, communication styles, and work expectations often trigger intergenerational conflict. This article aims to analyze the causes, impacts, and resolution strategies for generational conflict at work. Using a qualitative approach through literature review, the findings reveal that cross-generational understanding, effective communication, and inclusive leadership are key to fostering a harmonious and productive work environment. This research offers valuable insights for human resource management in handling generational diversity.